KONTRIBUSI PERBANKAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI SULAWESI SELATAN - Bayu Segara; Siti Radiatul Azzahra; Selvi Hardianti; Kamaruddin, Kamaruddin (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The aim of this research is to determine the influence of the dependent variables Total Assets, Third Party Funds, Financing (mudharabah, musyarakah, murabahah), and on the Economic Growth of South Sulawesi, specifically in the city of Makassar, which is represented by GDP as the dependent variable. The data used are financial reports from quarter 1 of 2017 to quarter 4 of 2020 sourced from Sharia Commercial Banks, Sharia Business Units, Central Statistics Agency, and the Financial Services Authority. The method used is Autoregressive Distributed Lag (ARDL) to see the long-term and short-term influence of the independent variable on the dependent variable. The research results show that Total Assets and ZISWAF have a significant positive effect in the long and short term on GDP. Third Party Funds have a significant long-term and short-term negative impact on GDP. Financing has a significant positive effect in the long term but in the short term it has a significant negative effect on GDP. Apart from that, simultaneously all independent variables have a significant positive effect on GDP.